Kinetics and Atomic Mechanisms of Structural Phase Transformations in Photoexcited Monolayer TMDCs. (29th January 2018) - Krishnamoorthy, Aravind; Bassman, Lindsay; Kalia, Rajiv K.; Nakano, Aiichiro; Shimojo, Fuyuki; Vashishta, Priya
ABSTRACT: Rapid transitions between semiconducting and metallic phases of transition-metal dichalcogenides are of interest for 2D electronics applications. Theoretical investigations have been limited to using thermal energy, lattice strain and charge doping to induce the phase transition, but have not identified mechanisms for rapid phase transition. Here, we use density functional theory to show how optical excitation leads to the formation of a low-energy intermediate crystal structure along the semiconductor-metal phase transition pathway. This metastable crystal structure results in significantly reduced barriers for the semiconducting-metal phase transition pathway leading to rapid transition in optically excited crystals.